5.20.13 Problems 1201 to 1300

Table 5.931: Second or higher order ODE with constant coefficients

#

ODE

Mathematica

Maple

5955

\[ {}y^{\prime \prime }+3 y^{\prime }+2 y = 8+6 \,{\mathrm e}^{x}+2 \sin \left (x \right ) \]

5956

\[ {}y^{\prime \prime }+y^{\prime }+y = x^{2} \]

5957

\[ {}y^{\prime \prime }-2 y^{\prime }-8 y = 9 x \,{\mathrm e}^{x}+10 \,{\mathrm e}^{-x} \]

5958

\[ {}y^{\prime \prime }-3 y^{\prime } = 2 \sin \left (x \right ) {\mathrm e}^{2 x} \]

5959

\[ {}y^{\prime \prime }+y^{\prime } = x^{2}+2 x \]

5960

\[ {}y^{\prime \prime }+y^{\prime } = x +\sin \left (2 x \right ) \]

5961

\[ {}y^{\prime \prime }+y = 4 x \sin \left (x \right ) \]

5962

\[ {}y^{\prime \prime }+4 y = \sin \left (2 x \right ) x \]

5963

\[ {}y^{\prime \prime }+2 y^{\prime }+y = x^{2} {\mathrm e}^{-x} \]

5964

\[ {}y^{\prime \prime }+3 y^{\prime }+2 y = {\mathrm e}^{-2 x}+x^{2} \]

5965

\[ {}y^{\prime \prime }-3 y^{\prime }+2 y = x \,{\mathrm e}^{-x} \]

5966

\[ {}y^{\prime \prime }+y^{\prime }-6 y = x +{\mathrm e}^{2 x} \]

5967

\[ {}y^{\prime \prime }+y = \sin \left (x \right )+{\mathrm e}^{-x} \]

5968

\[ {}y^{\prime \prime }+y = \sin \left (x \right )^{2} \]

5969

\[ {}y^{\prime \prime }+y = \sin \left (x \right ) \sin \left (2 x \right ) \]

5970

\[ {}y^{\prime \prime }-5 y^{\prime }-6 y = {\mathrm e}^{3 x} \]

5971

\[ {}y^{\prime \prime }-y^{\prime }-2 y = 5 \sin \left (x \right ) \]

5972

\[ {}y^{\prime \prime }+9 y = 8 \cos \left (x \right ) \]

5973

\[ {}y^{\prime \prime }-5 y^{\prime }+6 y = {\mathrm e}^{x} \left (2 x -3\right ) \]

5974

\[ {}y^{\prime \prime }-3 y^{\prime }+2 y = {\mathrm e}^{-x} \]

5975

\[ {}y^{\prime \prime }+y = \sec \left (x \right ) \]

5976

\[ {}y^{\prime \prime }+y = \cot \left (x \right ) \]

5977

\[ {}y^{\prime \prime }+y = \sec \left (x \right )^{2} \]

5978

\[ {}y^{\prime \prime }-y = \sin \left (x \right )^{2} \]

5979

\[ {}y^{\prime \prime }+y = \sin \left (x \right )^{2} \]

5980

\[ {}y^{\prime \prime }+3 y^{\prime }+2 y = 12 \,{\mathrm e}^{x} \]

5981

\[ {}y^{\prime \prime }+2 y^{\prime }+y = x^{2} {\mathrm e}^{-x} \]

5982

\[ {}y^{\prime \prime }+y = 4 x \sin \left (x \right ) \]

5983

\[ {}y^{\prime \prime }+2 y^{\prime }+y = {\mathrm e}^{-x} \ln \left (x \right ) \]

5984

\[ {}y^{\prime \prime }+y = \csc \left (x \right ) \]

5985

\[ {}y^{\prime \prime }+y = \tan \left (x \right )^{2} \]

5986

\[ {}y^{\prime \prime }+2 y^{\prime }+y = \frac {{\mathrm e}^{-x}}{x} \]

5987

\[ {}y^{\prime \prime }+y = \sec \left (x \right ) \csc \left (x \right ) \]

5988

\[ {}y^{\prime \prime }-2 y^{\prime }+y = {\mathrm e}^{x} \ln \left (x \right ) \]

5989

\[ {}y^{\prime \prime }-3 y^{\prime }+2 y = \cos \left ({\mathrm e}^{-x}\right ) \]

6135

\[ {}y^{\prime \prime }+y^{\prime }-2 y = 0 \]

6136

\[ {}y^{\prime \prime }-4 y^{\prime }+4 y = 0 \]

6137

\[ {}y^{\prime \prime }+9 y^{\prime } = 0 \]

6138

\[ {}y^{\prime \prime }+2 y^{\prime }+2 y = 0 \]

6139

\[ {}y^{\prime \prime }-2 y^{\prime }+6 y = 0 \]

6140

\[ {}y^{\prime \prime }+16 y = 0 \]

6141

\[ {}y^{\prime \prime }-5 y^{\prime }+6 y = 0 \]

6142

\[ {}y^{\prime \prime }+5 y^{\prime } = 0 \]

6143

\[ {}y^{\prime \prime }-4 y^{\prime }+13 y = 0 \]

6144

\[ {}2 y^{\prime \prime }+y^{\prime }-y = 0 \]

6145

\[ {}y^{\prime \prime }+\left (1+2 i\right ) y^{\prime }+\left (-1+i\right ) y = 0 \]

6146

\[ {}y^{\prime \prime }+\left (1+2 i\right ) y^{\prime }+\left (-1+i\right ) y = 0 \]

6147

\[ {}y^{\prime \prime \prime }+y = 0 \]

6148

\[ {}y^{\prime \prime \prime }+y^{\prime \prime }-6 y^{\prime } = 0 \]

6149

\[ {}y^{\prime \prime \prime }+3 y^{\prime \prime }-9 y^{\prime }-5 y = 0 \]

6150

\[ {}y^{\prime \prime \prime \prime }+4 y = 0 \]

6151

\[ {}y^{\prime \prime }-4 y^{\prime } = 10 \]

6152

\[ {}y^{\prime \prime }-4 y^{\prime }+4 y = 16 \]

6153

\[ {}y^{\prime \prime }+y^{\prime }-2 y = {\mathrm e}^{2 x} \]

6154

\[ {}y^{\prime \prime }-2 y^{\prime }-3 y = 24 \,{\mathrm e}^{-3 x} \]

6155

\[ {}y^{\prime \prime }+y = 2 \,{\mathrm e}^{x} \]

6156

\[ {}y^{\prime \prime }+6 y^{\prime }+9 y = 12 \,{\mathrm e}^{-x} \]

6157

\[ {}y^{\prime \prime }-y^{\prime }-2 y = 3 \,{\mathrm e}^{2 x} \]

6158

\[ {}y^{\prime \prime }-16 y = 40 \,{\mathrm e}^{4 x} \]

6159

\[ {}y^{\prime \prime }+2 y^{\prime }+y = 2 \,{\mathrm e}^{-x} \]

6160

\[ {}y^{\prime \prime }-6 y^{\prime }+9 y = 6 \,{\mathrm e}^{3 x} \]

6161

\[ {}y^{\prime \prime }+2 y^{\prime }+10 y = 100 \cos \left (4 x \right ) \]

6162

\[ {}y^{\prime \prime }+4 y^{\prime }+12 y = 80 \sin \left (2 x \right ) \]

6163

\[ {}y^{\prime \prime }-2 y^{\prime }+y = 2 \cos \left (x \right ) \]

6164

\[ {}y^{\prime \prime }+8 y^{\prime }+25 y = 120 \sin \left (5 x \right ) \]

6165

\[ {}5 y^{\prime \prime }+12 y^{\prime }+20 y = 120 \sin \left (2 x \right ) \]

6166

\[ {}y^{\prime \prime }+9 y = 30 \sin \left (3 x \right ) \]

6167

\[ {}y^{\prime \prime }+16 y = 16 \cos \left (4 x \right ) \]

6168

\[ {}y^{\prime \prime }+2 y^{\prime }+17 y = 60 \,{\mathrm e}^{-4 x} \sin \left (5 x \right ) \]

6169

\[ {}4 y^{\prime \prime }+4 y^{\prime }+5 y = 40 \,{\mathrm e}^{-\frac {3 x}{2}} \sin \left (2 x \right ) \]

6170

\[ {}y^{\prime \prime }+4 y^{\prime }+8 y = 30 \,{\mathrm e}^{-\frac {x}{2}} \cos \left (\frac {5 x}{2}\right ) \]

6171

\[ {}5 y^{\prime \prime }+6 y^{\prime }+2 y = x^{2}+6 x \]

6172

\[ {}2 y^{\prime \prime }+y^{\prime } = 2 x \]

6173

\[ {}y^{\prime \prime }+y = 2 x \,{\mathrm e}^{x} \]

6174

\[ {}y^{\prime \prime }-6 y^{\prime }+9 y = 12 x \,{\mathrm e}^{3 x} \]

6175

\[ {}y^{\prime \prime }-2 y^{\prime }-3 y = 16 x^{2} {\mathrm e}^{-x} \]

6176

\[ {}y^{\prime \prime }+y = 8 x \sin \left (x \right ) \]

6177

\[ {}y^{\prime \prime }+y = x^{3}-1+2 \cos \left (x \right )+\left (2-4 x \right ) {\mathrm e}^{x} \]

6178

\[ {}y^{\prime \prime }-5 y^{\prime }+6 y = 2 \,{\mathrm e}^{x}+6 x -5 \]

6179

\[ {}y^{\prime \prime }-y = \sinh \left (x \right ) \]

6180

\[ {}y^{\prime \prime }+y = 2 \sin \left (x \right )+4 x \cos \left (x \right ) \]

6181

\[ {}y^{\prime \prime }+2 y^{\prime }+y = 4 \,{\mathrm e}^{x}+\left (1-x \right ) \left ({\mathrm e}^{2 x}-1\right ) \]

6182

\[ {}y^{\prime \prime }-2 y^{\prime } = 9 x \,{\mathrm e}^{-x}-6 x^{2}+4 \,{\mathrm e}^{2 x} \]

6210

\[ {}y^{\prime \prime \prime }+2 y^{\prime \prime }+2 y^{\prime } = 0 \]

6211

\[ {}r^{\prime \prime }-6 r^{\prime }+9 r = 0 \]

6213

\[ {}y^{\prime \prime }+2 y^{\prime }+2 y = 10 \,{\mathrm e}^{x}+6 \,{\mathrm e}^{-x} \cos \left (x \right ) \]

6220

\[ {}y^{\prime \prime }+4 y^{\prime }+5 y = 26 \,{\mathrm e}^{3 x} \]

6221

\[ {}y^{\prime \prime }+4 y^{\prime }+5 y = 2 \,{\mathrm e}^{-2 x} \cos \left (x \right ) \]

6222

\[ {}y^{\prime \prime }-4 y^{\prime }+4 y = 6 \,{\mathrm e}^{2 x} \]

6223

\[ {}y^{\prime \prime }-5 y^{\prime }+6 y = {\mathrm e}^{2 x} \]

6227

\[ {}y^{\prime \prime }-2 y^{\prime }+5 y = 5 x +4 \,{\mathrm e}^{x} \left (1+\sin \left (2 x \right )\right ) \]

6229

\[ {}y^{\prime \prime \prime \prime }-2 y^{\prime \prime \prime }+13 y^{\prime \prime }-18 y^{\prime }+36 y = 0 \]

6234

\[ {}y^{\prime \prime }+y^{\prime }-6 y = 6 \]

6243

\[ {}y^{\prime \prime } = -4 y \]

6245

\[ {}y^{\prime \prime } = y \]

6247

\[ {}y^{\prime \prime }-2 y^{\prime }+y = 0 \]

6388

\[ {}x^{\prime \prime }-\omega ^{2} x = 0 \]

6389

\[ {}x^{\prime \prime \prime }-x^{\prime \prime }+x^{\prime }-x = 0 \]

6390

\[ {}x^{\prime \prime }+42 x^{\prime }+x = 0 \]

6391

\[ {}x^{\prime \prime \prime \prime }+x = 0 \]